Answer:
-23
Explanation:
We note that as x increases by 36 from -72 to 36, y decreases by 24 from 25 to 1.
Increasing x from -36 by another 36 to zero will correspond to a decrease in y by another 24 from 1 to -23.
The y-intercept is -23.
_____
You could go to the trouble to use these observations to compute the slope as -24/36 = -2/3. Then you could pick one of the points and write the equation in point-slope form as ...
y = -2/3(x +36) +1 . . . point-slope form with m=-2/3, (h, k) = (-36, 1)
y = -2/3x -24 +1 . . . . . eliminate parentheses
y = -2/3x -23 . . . . . . . y-intercept is -23